Sequential capsule endoscopy of the small bowel for follow-up of patients with known Crohn's disease. (1st December 2014) - Niv, Eva; Fishman, Sigal; Kachman, Helena; Arnon, Ruth; Dotan, Iris
Abstract: Background and Aims: The aim of this study was to perform sequential small bowel (SB) capsule endoscopy (CE) studies in patients with known active Crohn's disease (CD) during different treatments, to characterize the changes in the SB mucosa over time, and to correlate the CE findings with clinical and laboratory parameters of inflammation. Methods: Consecutive patients with known moderately active CD were prospectively recruited. After proven patency with Agile capsule, CE studies were performed at baseline and after 4, 12 and 24 weeks. CE parameters and a Lewis score were calculated. Clinical and laboratory parameters were correlated. A control group of 178 non-CD patients was used for comparisons. Results: Thirty-one CD patients were recruited and 19 met the inclusion criteria. A total of 43 CE studies were performed over the time. There was no capsule retention despite a high rate of previous SB surgery. The mean baseline CDAI, IBDQ and Lewis scores were 306 ± 56, 135 ± 26.6 and 1730 ± 1780, respectively. There was no correlation at the baseline between clinical and laboratory parameters (CDAI, CRP, IBDQ) and mucosal disease (Lewis scores). CDAI and IBDQ changes over a period of 4 and 12 weeks did not correlate with the Lewis score. The cecum arrival rate of the CD patients was significantly lower (p = 0.0047) and the SB transit time was significantly longer (p = 0.005) compared to those of the controls. Conclusions: Sequential CE studies are feasible and safe in CD patients. In patients with complete CE studies, they provide reliable information on mucosal changes in CD and should be considered as an independent and objective follow-up tool in known CD patients.